Capillary electrophoresis : theory & practice - Grossman, Paul D.; Colburn, Joel C. (Academic Press, 1992)
This book is designed to be a practical guide, used by wide audience, including those new to CE, those more experienced, routine users, those interested in technology development, and those involved with applications research. References have been emphasized to allow the reader to explore the detailed specifics and theoretical foundations. This book draws together the rapidly evolving, diverse, and multidisciplinary subject of capillary electrophoresis (CE). It is designed as a practical guide to be used by a wide audience, including those new to CE as well as more experienced users. This volume presents the capabilities, limitations, potentials, and future challenges facing each area of CE. Key aspects of this technique, such as high resolution capability, full automation, high speed separations, quantification of nanoliter sample volumes, and simultaneous multiple detection capabilities are presented in a concise and logical fashion. This book is designed to help you make the most of your CE separations, and includes comprehensive information on: Electroosmosis, separation efficiency, and Joule heating Detection methods In-depth discussion of the separation principles and capabilities of the major modes of CE Sieving gel electrophoresis Isoelectric focusing Free solution CE Micellar electrokinetic capillary chromatography Entangled polymer matrix-based separation Detailed treatment of the application of CE to a wide range of molecules, supplemented with extensive "hands-on" illustrations